Способ получения жидкого стекла гидротермальным методом - Лотов В. А. Василий Агафонович; Верещагин В. И. Владимир Иванович; Косинцев В. И. Виктор Иванович; Пасечников Ю. В.
опубл. 10.07.99, Бюл. № 19